Exploring beneficiary perceptions about the use of refurbished container classrooms for early childhood development in vulnerable communities in the Westen Cape - Mwape, Christine (Department of Social Development, 2014)
This study explored beneficiary perceptions about the use of refurbished container classrooms for Early Childhood Development (ECD) in vulnerable communities in the Western Cape. It was conducted on a sample of three ECD centres, one at Philippi and two at Khayelitsha. Key informants at each centre included the Principal, two teachers, three community leaders and a focus group of up to six parents. The study used the qualitative approach and employed a purposive sampling technique. Semi-structured interview schedules, developed in line with the research objectives, were used to guide the interviews. The study revealed that the container classrooms were safer and healthier ECD facilities compared to the shacks previously used. They were used as childcare and early learning facilities and also for community activities. Challenges experienced in using container classrooms were around maintenance of the structures and intermittent funding;; while measures considered essential in enhancing usage of container classrooms included the provision of spacious classrooms;; supporting facilities (toilets and kitchen);; creating a stimulating play space around the container, and greater stakeholder participation in the running of the centres. The research makes the following recommendations: i. That further research be done towards an understanding of the extent, nature and impact of the container facilities concept at national level;; ii. To Breadline Africa that community involvement in the monitoring process be enhanced and to responde to the need to adjust the physical structures to enhance durability and withstand extreme weather conditions;; and iii. To the Department of Social Development to review its funding strategies and to consider investing in infrastructure in low socio-economic communities as a way of ensuring availability of acceptable standards of ECD centres for poor children.